A study on the effects of english lecturers' nonverbal communication among the student's interest in the english language in faculty of business management at Universiti Teknologi Mara (UITM) Cawangan Pahang / Nora Asyikin Ahmad - Ahmad, Nora Asyikin (2013)
The purpose of this study was to determine the effects of English lecturers' non-verbal communication on student's interest in the English language among the student in Faculty of Business Management at Universiti Teknologi MARA (UiTM) Cawangan Pahang. The population of this study was selected among the degree students of Office Systems Management in Centre of Applied Management Studies. This paper was descriptively shown how the elements of non-verbal communication were applied in order to know the effectiveness towards student's interest regarding to the English subject. The elements that have been analyzed were facial expression, eye contact, gesture and pitch of voice. Furthermore, this paper also examined the student's perception and problems arise in practicing non-verbal communication among lecturers' on student's interest in the English language. Based on the student's perception, this paper was analyzed on how the students thought about using the four elements of non-verbal communication. Meanwhile, the problem arises regarding of non-verbal communication to describe the factors that contribute to the lecturers when using non-verbal communication. This study focused on the degree students of Office Systems Management that took English subject in their courses. The data was gathered by using the questionnaires method that had answered by 68 of the students from semester two until semester four.